(untitled) (REMUNOM, 2024)
The article addresses the issue of occupational accidents in Cascavel, Paraná, highlighting the complexity of these events and their relevance as a social problem. The study analyzes data from the National System of Injuries and Notifications (SINAN) from 2022, revealing that the majority of cases resulted in medical care. Aspects such as the low issuance of the Work Accident Report (CAT) and the most common causes, such as impacts by objects and traffic accidents, are discussed. The research emphasizes the need for effective public policies and supervision to enhance prevention and care for injured workers in Cascavel.